PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA YOGYAKARTA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Nugroho, Desi; Wikaningtyas, Suci Utami (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study entitled The Influence of Leadership Style, Organizational Culture, and Motivation on the Performance of Yogyakarta Primary Service Office Employees with Job Satisfaction as an Intervening Variable. The purpose of this study was to examine and analyze the influence of Leadership Style, Organizational Culture, and Motivation partially or simultaneously on the Performance of Yogyakarta Primary Service Office Employees with Job Satisfaction as an Intervening Variable. The population in this study are employees of the Yogyakarta Primary Tax Service Office in 2023, of which there are 105 employees. This study used a saturated sample so that all populations were sampled. The data used in this study are primary data obtained directly from research subjects by distributing questionnaires to 105 respondents. This research was conducted using the Structural Equation Model (SEM) through the Partial Least Square (PLS) approach with the help of the SmartPLS ver. 3.2.9 for Windows.The results of this study indicate that leadership style has no effect on employee performance but has a positive and significant effect on job satisfaction. Organizational Culture Has No Influence on Employee Performance but Has a Positive and Significant Influence on Job Satisfaction. Motivation has a positive and significant impact on both employee performance and job satisfaction. Job Satisfaction Has a Positive and Significant Influence on Employee Performance. Job Satisfaction as an Intervening variable is able to mediate the Influence of Leadership Style, Organizational Culture, and Motivation on Employee Performance.